Cardiac Dysfunction with Progressive Muscular Dystrophy a Case Report - Gülmen, Mete Korkut; Bilgin, Nursel Gamsız; Çekin, Necmi; Alper, Benhan; Hilal, Ahmet (The Bulletin of Legal Medicine, 2004)
The cause in sudden postmortem mostly differs in various countries in relation to the quality and range of health care systems. We wanted to present a Progressive Muscular Dystrophy case in which we had diagnostic problems. From the death examination and autopsy files, which were sent to Morgue Department of Adana Branch of the Forensic Medicine Council, it is learned that the prosecutor was informed for the case who died at home and the autopsy was performed at the State Hospital Morgue. As no special finding was detected by the external examination of the body and macroscopic examination of the organs, samples were obtained for the histopatologic and toxicologic evaluation. Myocardial signs consistent with the Duchene Muscular dystrophy were detected by the histopatologic examination of the myocardial sections that performed in the Çukurova University Medical Faculty Hospital Departments of Forensic Medicine. For this case, cardiac involvement that occurred in the clinical course of the progressive muscular dystrophy was accepted as the death cause. In this report, a case of progressive muscular dystrophy, the first case that was detected by the Çukurova University Medical Faculty Hospital Departments of Forensic Medicine was discussed in the light of the references for the interest of forensic medicine members.Key words: Progressive Muscular Dystrophy, Sudden death, Forensic Pathology, Autopsy.
Keywords: progressive muscular dystrophy; sudden death; forensic pathology; autopsy